NEPTU DALAM PRASASTI JAWA BALI (MAKNA PSIKO-RELIGIUS) - Hari Lelono (BRIN, 1994)
Humans as part of nature have a culture that is embraced and believed, both consciously and unconsciously. One of the visible elements of culture is material culture in the form of written works with beautiful poetry, these works in the form of inscriptions.